PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA MATERI MEMBACA PEMAHAMAN KELAS 4 DI MADRASAH IBTIDAIYAH AL-BAROKAH AN-NUR AJUNG, JEMBER - Eva Nur Khofifah; Hartono Hartono (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2023)
This study aims to determine the application of the CIRC type Cooperative Learning learning model in reading comprehension material for grade 4 at Madrasah Ibtidaiyah Al Barokah An-Nur Ajung, Jember. This research was conducted due to the background in which students find it difficult to understand and find information on a reading text and on the other hand students also have problems, namely they are easily bored in following lessons in class. Then the class teacher decided to apply the CIRC learning model, therefore researchers were interested in conducting research on the application of the CIRC learning model. The subjects of this study were fourth grade students. This study used a qualitative method. Data collection techniques using observation, interviews and documentation. Data analysis uses condensation, data display and conclusion drawing. The results of this study indicate that with the application of the CIRC learning model, students can easily understand and obtain information about the content of reading texts. Where in the implementation of the CIRC learning model students are required to work in groups so that students gain new experiences in learning, besides that students will be more confident in expressing their opinions in group learning.